Nitrogen depletion in the fission yeast Schizosaccharomyces pombe causes nucleosome loss in both promoters and coding regions of activated genes - Kristell, Carolina; Orzechowski Westholm, Jakub; Olsson, Ida; Ronne, Hans; Komorowski, Jan; Bjerling, Pernilla (Genome Research, 2010)
Gene transcription is associated with local changes in chromatin, both in nucleosome positions and in chemical modifications of the histones. Chromatin dynamics has mostly been studied on a single-gene basis. Those genome-wide studies that have been made primarily investigated steady-state transcription. However, three studies of genome-wide changes in chromatin during the transcriptional response to heat shock in the budding yeast Saccharomyces cerevisiae revealed nucleosome eviction in promoter regions but only minor effects in coding regions. Here, we describe the short-term response to nitrogen starvation in the fission yeast Schizosaccharomyces pombe. Nitrogen depletion leads to a fast induction of a large number of genes in S. pombe and is thus suitable for genome-wide studies of chromatin dynamics during gene regulation. After 20 min of nitrogen removal, 118 transcripts were up-regulated. The distribution of regulated genes throughout the genome was not random; many up-regulated genes were found in clusters, while large parts of the genome were devoid of up-regulated genes. Surprisingly, this up-regulation was associated with nucleosome eviction of equal magnitudes in the promoters and in the coding regions. The nucleosome loss was not limited to induction by nitrogen depletion but also occurred during cadmium treatment. Furthermore, the lower nucleosome density persisted for at least 60 min after induction. Two highly induced genes, urg1+ and urg2+, displayed a substantial nucleosome loss, with only 20% of the nucleosomes being left in the coding region. We conclude that nucleosome loss during transcriptional activation is not necessarily limited to promoter regions.